Different hydrophilic polyglycerol fatty acid esters interact with fat crystals and proteins at the interface to co-stabilize highly unsaturated whipped emulsions - Han, Wanjun; Chai, Xiuhang; Sun, Yanwen; Zaaboul, Farah; Tan, Chin-Ping; Liu, Yuanfa (Elsevier BV, 2024)
This study investigates the impact of different hydrophilic polyglycerol fatty acid esters (SWA-10D, M-7D and M-10D) on the stability of aerated emulsions containing palm oil stearin (solid fat content of 6 w/w) under varying pressures. The study encompasses a comparative analysis of the microstructure of droplets, distribution of fat crystals, and protein at the interface within these distinct emulsions. In addition, the study evaluates the stability of the emulsions after a whipping process. The microstructure of emulsions prepared with M-7D showed discernible evident bright rings that become more pronounced as pressure increased. Furthermore, the droplet size of M-7D emulsion was consistently smaller in comparison to M-10D and SWA-10D emulsions at different pressure levels. The M-7D emulsion exhibited a higher nucleation rate, featuring a greater count of crystal nuclei at the interface. Simultaneously, the interfacial protein content in the M-7D emulsion was lower compared to the other samples, diminishing from 2.5 mg/mL to 0.6 mg/mL as pressure increased. Consequently, the interface accommodated a higher concentration of interfacial fat crystals, while the protein content decreased, resulting in increased partial coalescence. This phenomenon, in turn, promoted the formation of a sharp rosette-shaped aerated structure, leading to a diminutive reduction of less than 10 in height over 6 h. This outcome serves as a clear indicator of the formation of a stable aerated structure.